In vitro Naringenin SNEDDS Release Test by Dissolution - Gendis Purno Yudanti; Ilham Kuncahyo; Endang Diyah Ikasari (HM Publisher, 2023)
Naringenin is the main flavanone in grapefruit which has anti-inflammatory, anti-cancer, hepatoprotective and antilipid peroxidation effects. Its low solubility in water causes dissolution and low bioavailability when taken orally. This study aims to increase the solubility and bioavailability of naringenin by using the SNEDDS technique. Initial characterization to determine the optimum formula was carried out using the D-optimal mixture design method, namely by optimizing the composition of SNEDDS which consisted of triacetin as the oil phase, tween 80 as surfactant and transcutol P as cosurfactant as an independent factor and SNEDDS characterization included emulsification time, drug loading, size globules and percent transmittance in response. The optimization results showed that the optimum formula was obtained at the composition of 10% triacetin, 70% tween 80 and 20% transcutol P. The dissolution test showed that the SNEDDS of naringenin was capable of dissolution (Q30) of 87,50% ±1,73 at the 30th minute and the f2 value of 28,93 so it can be concluded that the dissolution profile between the SNEDDS of naringenin and the naringenin capsules is not identical.